THE EFFECT OF EMPLOYABILITY, WORK MOTIVATION, AND LEADERSHIP ON JOB SATISFACTION OF GENERATION Z EMPLOYEES IN MEDAN CITY - Susanna Silvia Sembiring; Esther Praja Anggriany Panggabean (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study aims to determine the effect of employability, work motivation, and leadership on the job satisfaction of Generation Z employees in Medan City. This study uses a causal quantitative approach by distributing questionnaires to 170 Generation Z employee respondents in Medan City. The sampling technique used purposive sampling with the criteria of employees born between 1997–2012 and actively working in Medan City. The sample size was determined following Hair et al. (2013) with 16 indicators multiplied by 10. The data analysis technique used Partial Least Square – Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results showed that: (1) employability has a positive and significant effect on job satisfaction (T=3.810; P=0.000); (2) work motivation has a positive and significant effect on job satisfaction (T=9.900; P=0.000); (3) leadership has a negative and significant effect on job satisfaction (T=1.992; P=0.047). Simultaneously, all three variables have a significant effect with F-count 77.04 > F-table 3.054. The R² value of 0.582 indicates that 58.2% of the variation in job satisfaction is explained by the three variables.